Prediction of Stability Limits for Binary and Ternary Systems Using the NTRL Liquid Phase Model - Al-Sadoon, Fahad M. (2013)
A Master of Science thesis in Chemical Engineering by Fahad M. Al-Sadoon entitled, "Prediction of Stability Limits for Binary and Ternary Systems Using the NTRL Liquid Phase Model," submitted in January 2013. Thesis advisor is Dr. Naif Darwish. Available are both soft and hard copies of the thesis.